Factors Affecting the Turnover Intention of Indonesian Radiographers during the Covid-19 Pandemic - Ahmad Hariri Sokhibi; Wilda Wahyuni; Agus Rochmat; Abdul Gamal Sukaryono; Achmad Hasmy (PT FORMOSA CENDEKIA GLOBAL, 2023)
Radiographers are one of the frontlines of covid 19 patient services, including professions affected by the covid 19 pandemic. This study was conducted to prove the effect of Work Engagement (WE), Job Satisfaction (JS), Quality of Work Life (QWL) and Job Stress (JSt) and on radiographers Turnover intention (TI) during the Covid 19 pandemic, using an online survey of Indonesian radiographers, collected 243 respondents and used the SEM-Amos analysis technique version 24 in its hypothesis test. The results of the analysis prove that Work Engagement and Job Satisfaction have a negative effect on Turnover Intention, while Quality of Work Life does not affect Turnover Intention and Job Stress has a significant positive effect on Turnover Intention. Of the four factors, work stress is the most influential factor in the turnover intention of a radiographer during the Covid-19 pandemic. Research findings found that radiographers' turnover intention is greatly influenced by job stress, and this is very beneficial for hospital managers in maintaining their radiographers, especially during this pandemic